EZH2 restricts Tcf7 DNA methylation and promotes TFH differentiation during acute viral infection - Luo, Yuan; Li, Dan; Xie, Luoyingzi; Lei, Shun; Chen, Xiangyu; Wang, Cong; Yao, Dong; Li, Lin; Fang, Jingyi; Chen, Cheng; Yuan, Shijie; Li, Fei; et al. (Frontiers in Immunology, 2022)
Follicular helper T (TFH) cells provide specialized help for B cells to ensure optimal humoral immunity. The histone methyltransferase EZH2, as a chromatin repressor, secures the TFH differentiation by promoting TFH lineage associated gene expression during acute viral infection, including Tcf7 and Bcl6. By using conditional deletion murine system, we observed that EZH2 ablation in CD4+ T cells was accompanied by aberrant accumulation of DNA methyltransferases (DNMTs) DNMT1 and DNMT3B in TFH cells. And the loss of EZH2 promoted aggravation of DNA methylation status at Tcf7 locus. Therefore, our findings suggested that EZH2 plays an important role in maintenance of hypomethylation at Tcf7 locus thus affecting TFH differentiation during acute viral infection.